New or little known Palaearctic species of Platygastrinae (Hymenoptera: Platygastridae). II. - Buhl, Peter (Entomologica Fennica, 2005)
Seven species new to science are described and their affinities discussed, viz. Anopedias notaulatus (Finland), Inostemma koponeni (Finland and Poland), Piestopleura canariensis (Canary Islands), Platygaster anopediana (Finland), P. oblonga (Finland), Synopeas bialowiezaensis (Poland), and S. discoideus (Finland). The males of Leptacis breisteini Buhl, 1997, L. coryphe Buhl, 1998, L. vlugi Buhl, 1997, Platygaster marttii Buhl, 2003, and Synopeas brevis Buhl, 1998, previously unknown to science, are described.